(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The present paper deals with botanical description and new distributional record for Meremia hederacea (Brum.f.) Hallier f. and Ipomoea marginata (Desr.) Verdc. forma marginata belonging to family Convolvulaceae. These species have been recorded from Gujarat from new localities in Banaskantha district of Gujarat state. It is provided here with description, photographs, habitat ecology, phenology, conservations measures for facilitating the identification and conservation measures.